Evaluasi Dan Tindak Lanjut Program Pengembangan Fisik Motorik Anak Usia Dini Di TK Pertiwi DWP - Siti Nuramita; Maesun Mia Nur Amalia; Azka Putri Ayuning Tyas Azis; Dhea Mutiara Indah; Risa Muplihah (Sekolah Tinggi Agama Islam Al-Kifayah Riau, 2026)
This study aims to describe the implementation of a physical motor skills development program for early childhood, with a particular focus on evaluation and follow-up at Pertiwi Kindergarten DWP. The program is designed to understand how this development is systematically implemented to support holistic child development. The research method used is a qualitative approach, with data collection techniques including direct observation, in-depth interviews, and documentation of daily activities. This approach allows for authentic and comprehensive data collection on the motor skill development process. Implementation results indicate that gross and fine motor skill development is carried out in a structured manner and adapted to the child's developmental stage, using engaging and experience-based methods to increase child participation. Program evaluation is carried out continuously by educators through observation sheets and daily checklists that include motor development indicators, with assessments carried out by educators who are most competent in understanding the child's abilities. The evaluation results then serve as the basis for formulating follow-up learning, such as providing additional activities for children who have met the indicators or additional guidance for those who need it. Overall, this program demonstrates systematic, authentic implementation and is tailored to the child's individual abilities, thus contributing to optimal motor development